EMT-Mediated Acquired EGFR-TKI Resistance in NSCLC: Mechanisms and Strategies - Zhu, Xuan; Chen, Lijie; Liu, Ling; Niu, Xing (Frontiers in Oncology, 2019)
Acquired resistance inevitably limits the curative effects of epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs), which represent the classical paradigm of molecular-targeted therapies in non-small-cell lung cancer (NSCLC). How to break such a bottleneck becomes a pressing problem in cancer treatment. The epithelial-mesenchymal transition (EMT) is a dynamic process that governs biological changes in various aspects of malignancies, notably drug resistance. Progress in delineating the nature of this process offers an opportunity to develop clinical therapeutics to tackle resistance towards anticancer agents. Herein, we seek to provide a framework for the mechanistic underpinnings on the EMT-mediated acquisition of EGFR-TKI resistance, with a focus on NSCLC, and raise the question of what therapeutic strategies along this line should be pursued to optimize the efficacy in clinical practice.